Minimal gauge vitrectomy for optic disc pit maculopathy: Our results - Kumar, Atul (Indian J Ophthalmol, 2015)
The purpose of the study was to describe the surgical technique and clinical outcomes of pars plana vitrectomy without laser or gas tamponade in cases with optic disc pit maculopathy at our centre. Six eyes of six consecutive patients presenting with unilateral optic disc pit maculopathy were enrolled. Preoperative optical coherence tomography (OCT) was performed to determine the presence and extent of schisis and macular detachment. All eyes underwent 23-gauge pars plana vitrectomy with induction of posterior vitreous detachment (PVD) and internal limiting membrane (ILM) peeling and eyes were closed under fluid. Patients were followed up for at least 12 months post-surgery. Median age of patients was 22.5 years. Five of six eyes had neurosensory detachment (NSD) at the presentation; whereas, inner layer schisis was present in all patients. None of the patients had any evidence of vitreomacular or vitreopapillary adhesion or PVD either clinically or on OCT. Inner and outer retinal schisis resolved in all eyes after follow-up of at least 6 months. Resolution of subretinal fluid in eyes with NSD was seen in 4 of 5 eyes. There was a significant visual acuity improvement from mean preoperative visual acuity of 0.79 logarithm of the minimum angle of resolution (logMAR) units to 0.36 logMAR units at 12 months (P = 0.001). Thus, vitrectomy with ILM peeling and PVD induction alone could achieve good functional outcomes in cases with optic disc pit maculopathy.